2002
DOI: 10.1148/radiol.2223010812
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Differential Protease Expression in Breast Cancers for Detection of Aggressive Tumor Phenotypes

Abstract: Cathepsin-B enzyme activity can be determined in vivo with NIRF optical imaging, while differences in tumoral expression may correlate with tumor aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(93 citation statements)
references
References 22 publications
0
92
0
1
Order By: Relevance
“…From a molecular-imaging perspective, ACPPDs have several advantages over other targeted fluorescent probes previously described in the literature for use in a surgical system (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Molecular fluorescence-guided surgery demands that a given probe (a), works for a wide variety of tumor types (b), offers ample signal with low background (c), binds tightly to the tumor, and (d), is not affected by the physical trauma of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a molecular-imaging perspective, ACPPDs have several advantages over other targeted fluorescent probes previously described in the literature for use in a surgical system (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). Molecular fluorescence-guided surgery demands that a given probe (a), works for a wide variety of tumor types (b), offers ample signal with low background (c), binds tightly to the tumor, and (d), is not affected by the physical trauma of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These probes are applicable to a wide range of tumors but are limited by contrast and nonspecificity. Other options that offer similar fluorescence contrast to ACPPD are the dequenching probes designed by Weissleder's group (19,20), peptide-based probes that target an abundant ligand such as the αvβ3 integrin (21), or 5-aminolevulinic acid (5-ALA) and derivatives, which get converted to fluorescent protoporphyrin IX in many tumors (22,23). All of these alternatives are limited to fluorescence readout, whereas ACPPD also allows MRI, whose noninvasive depth penetration and tomographic accuracy are ideally complementary to the high spatial resolution, real-time capability, and surgical compatibility of fluorescence.…”
Section: Discussionmentioning
confidence: 99%
“…An example of the signal sensitivity that can be achieved using these agents is the visualization of MMP-2 activity [50], [51], and [52]. In vitro, the authors observed an 850% increase in NIR fl uorescence intensity when the probe was cleaved and specifi c activation could be blocked by MMP-2 inhibitors.…”
Section: Activatable Probesmentioning
confidence: 99%
“…For in vivo imaging applications, the dye/protein ratio of the conjugate may affect biological or biochemical activity of the protein, signal-to-background ratio, clearance, and biodistribution [52]. The optimal ratio of coupling is unique to each targeting agent.…”
Section: Conjugating Probes With Nir Dyesmentioning
confidence: 99%
“…Alternatively, specificity might be enhanced by designing smart fluorescence probes, which are activated by interaction with the target tissue (e.g., enzymatic cleavage or oxidation) [113]. Bremer et al, for instance, showed in a mouse model that enzymatic activation of fluorescent probes induces up to 1.5 times higher fluorescence in undifferentiated breast cancer compared with well differentiated cancer [115,116].…”
Section: Discussionmentioning
confidence: 99%